Exploring the Essence of Fieldwork Training:A Phenomenological Study of Social Work Professionals - Bharadwaj, Yatheesh; M, Sivaranjini; Koshy, Ancy Sara (Medha: A Multidisciplinary Journal, 2026)
Social work is a practice-based profession and academic discipline that helps individuals and communities address psychosocial issues, promote positive social change, and improve overall well-being, and requires adequate exposure and training during Social Work education. Fieldwork is considered an integral part of social work training, as it connects theoretical learning with practical application. It also allows candidates to work with diverse populations and communities, gaining practical experience in addressing social problems. The role of fieldwork in shaping professional identity, developing practical skills, and fostering reflective practice has been well documented, yet students experience several challenges during the fieldwork placements. This research explored the lived experiences of social work students during their fieldwork training using a Phenomenological Approach. In-depth interviews were conducted with seven social work students who completed fieldwork placements. The findings showed that fieldwork is crucial for bridging the gap between theory and practice. Key themes included: (1) bridging theory and practice, (2) development of professional competencies, (3) building emotional strength and personal growth, (4) the importance of supervision and peer support, and (5) formation of professional identity. While participants faced several challenges, fieldwork training helped them become more skilled, emotionally stronger, and clearer about their professional role as social workers. Hence, fieldwork remains a cornerstone in social work education; it shapes competent, resilient, and reflective practitioners.